The Inflammation in the Cytopathology of Patients With Mucopolysaccharidoses- Immunomodulatory Drugs as an Approach to Therapy - Wiesinger, Anna-Maria; Bigger, Brian; Giugliani, Roberto; Scarpa, Maurizio; Moser, Tobias; Lampe, Christina; Kampmann, Christoph; Lagler, Florian B. (Frontiers in Pharmacology, 2022)
Mucopolysaccharidoses (MPS) are a group of lysosomal storage diseases (LSDs), characterized by the accumulation of glycosaminoglycans (GAGs). GAG storage-induced inflammatory processes are a driver of cytopathology in MPS and pharmacological immunomodulation can bring improvements in brain, cartilage and bone pathology in rodent models. This manuscript reviews current knowledge with regard to inflammation in MPS patients and provides hypotheses for the therapeutic use of immunomodulators in MPS. Thus, we aim to set the foundation for a rational repurposing of the discussed molecules to minimize the clinical unmet needs still remaining despite enzyme replacement therapy (ERT) and hematopoietic stem cell transplantation (HSCT).